180 days of problem solving for kindergarten - Hathaway, Jessica (Shell Education, 2017)
Help kindergarten students improve critical-thinking and reasoning skills with fun and effective daily practice activities. Focusing on one skill each week, students will learn the problem-solving process: think, plan, solve, and explain.
Keywords: Mathematics -- Study and teaching (Preschool) -- United States.; Mathématiques -- Étude et enseignement (Préscolaire) -- États-Unis.; Mathematics -- Study and teaching (Preschool); United States